(untitled) (Journal of Philosophy Culture and Political Science, 2015)
The article provides insights into the country’s migration policies regarding Oralmans as well as the actual situation with their social, economic, and cultural integration. While focusing mainly on the findings of the survey of International organization of migration, also article describes government activities and schemes pertaining to Oralmans. The article analyzes the historical background of ethnic immigration in Kazakhstan. Authors describe government policies regarding oralmans in the country as well as the measures to encourage their arrival and to provide integration assistance. Also it is given general information about Oralmans in Kazakhstan, and geographical distribution in the territory of Kazakhstan and describe oralmans’ integration.